2022
DOI: 10.3390/jcm11247458
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life in Head-and-Neck Oncologic Patients with Intraoral Soft-Tissue Defects Reconstructed with Buccinator Myomucosal Flap

Abstract: The aim of this study is to evaluate the functional outcomes and quality of life (QoL) in oncologic patients with intraoral defects reconstructed with the buccinator myomucosal flap. A retrospective study was performed involving 39 patients with intraoral soft-tissue defects, reconstructed with a buccinator myomucosal flap during a six-year period. Patients completed the European Organization for Research and Treatment of Cancer questionnaires, the standard questionnaire (QLQ-C30) and the head-and-neck specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…-Radioterapia. Aunque existen trabajos que no hallan peores resultados de CV por radioterapia en cáncer de laringe y orofaringe (45), la mayoría reporta un efecto negativo (25,30).…”
Section: Cuestionarios Genéricosunclassified
“…-Radioterapia. Aunque existen trabajos que no hallan peores resultados de CV por radioterapia en cáncer de laringe y orofaringe (45), la mayoría reporta un efecto negativo (25,30).…”
Section: Cuestionarios Genéricosunclassified
“…Colella et al [11 ▪▪ ] emphasized its suitability for comorbid patients with poor systemic conditions. Recent studies assessing the quality of life and functional outcomes in head and neck oncologic patients following BMM flaps to reconstruct intraoral soft-tissue defects, found that prior radiation and neck dissection are not a contraindication to its use [24 ▪ ,25 ▪ ].…”
Section: Buccinator Myomucosal Flapmentioning
confidence: 99%
“…Potential complications of Bozola's flap mirror other loco-regional flaps and include partial necrosis of the flap necessitating removal of the ischaemic portion, complete flap failure, orocutaneous fistula and parotid duct damage. A reduction in mouth opening due to contracture (may require Z-plasty) and limitation of tongue mobility requiring detachment of the flap pedicle as well as temporary deficit of orbicularis oris have been reported [11 ▪▪ ,24 ▪ ,25 ▪ ]. Advantages of this flap are numerous, including short operative times (< 1 h), no requirement for microsurgery, a reduced complication rate with good quality of life and aesthetic outcome (owing to the use of intra oral incision and minimal donor site morbidity) [11 ▪▪ ,23,24 ▪ ,25 ▪ ].…”
Section: Buccinator Myomucosal Flapmentioning
confidence: 99%
See 2 more Smart Citations